Impact of sustainability integrating environmental and social practices on farm resilience: a quantitative study of farmers facing the post-COVID-19 economic turbulence in Japan - Yoshida, Shingo (Frontiers in Sustainable Food Systems, 2024)
Research on sustainability practices and resilience in farm systems has focused on the mutual interrelationship between the two. When identifying critical variables related to sustainability, it is essential to take an integrated perspective that considers the interplay among sustainable practices and uses a dataset that includes both environmental and social indicators. Thus, this study aims to quantitatively identify the impact of integrated sustainability indices on farm resilience, which is classified as persistence and adaptation, in the face of Post-COVID-19 economic turbulence. We obtained data from a questionnaire survey of 4,604 farms conducted by a government financial institution. Integrated sustainability indices and resilience indices are formulated through the application of factor analysis. As a result, we develop six sustainability indices that integrate environmental and social practices. A regression analysis reveals a positive correlation between the integrated sustainability indices and short-term persistence as farm resilience. Moreover, these sustainability indices exhibit a more pronounced impact on long-term adaptive resilience. These results imply that the integrated sustainability indices are more adept at evaluating farmers' sustainability endeavors and clarifying the relationship between sustainability and farm resilience than traditional environmental and social sustainability indicators.